Juridical Review of the Responsibility of the Recipient of Entrusted Timber Forest Products (Study of Decision Number 50/Pid.B/LH/2021/PN Slw) - Hadisiswoyo, Reviera Zahwa (Proceedings Series on Social Sciences & Humanities, 2023)
Illegal logging occurs lot in Indonesia, illegal logging is carried out by person or group of people who cut down forest without permit from government. Illegal logging usually carried out in areas that are prone to desertion and lack of supervision from government. In Indonesia, there are many areas that are rampant with illegal logging. One of them is Tegal Regency area, precisely in the Forest Management Unit (KPH) in Balapulang. An example of case is receipt of entrustment and storing timber forest products originating from KPH Balapulang. This research aims to find out and analyze judge's decision and analyze the existence of Certificate of Legality of Timber Forest Products in decision. The research method uses juridical-normative, focusing on normative law on laws and regulations related to forest destruction. The judge's verdict Number 50/Pid.B/LH/2021/PN Slw in practice is in accordance with Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, this because in verdict, defendant has fulfilled the elements in Article 87 Paragraph (1) letter c of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. The existence SKSHHK is important in Decision Number 50/Pid.B/LH/2021/PN Slw, because Certificate of Legality of Timber Forest Products is document that must be owned by every person who transports forest timber. This stated in Article 16 of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. The government is expected to conduct socialization about timportance of protecting forests to community.